THE EFFECT OF SERVICE QUALITY ON PATIENT LOYALTY MEDIATED BY PATIENT SATISFACTION IN BALI SILOAM HOSPITAL - I Made Adhi Mahendrayana; Putu Ngurah Suyatna Yasa; Luh Putu Indiani (Universitas Warmadewa, 2018)
Favorable Service Quality is one of the objectives in the implementation of health service at Bali Siloam Hospital synergizing with patient satisfaction to provide customer loyalty. This study aims at determining the effect of Service Quality on Patient Loyalty with Patient Satisfaction Mediation at Bali Siloam Hospital. The research method used was quantitative descriptive. Data analysis techniques used was multivariate statistical techniques of Partial Least Squares (PLS) method. The sample of this research was inpatient at Bali Siloam Hospital consisting of 100 respondents. The results of the study showed that Service Quality has a positive and significant effect on Patient Satisfaction with a significance value of 0.29. Service Quality positively and significantly influencing to Patient Loyalty with significance value equal to 0.39. Patient Satisfaction has positive and significant effect on Patient Loyalty with significance value of 0.56. Patient Satisfaction has a positive and significant influence in mediating the influence of Service Quality on Patient Loyalty with significance value of 0.469. Bali Siloam Hospital is advised to provide better supporting facilities, to improve the empathy of nurses while providing services to inpatients, and to provide certainty of information provided services, to create patient satisfaction, which would ultimately impact on increasing patient loyalty.